Synthesis of networks and interenetrating networks of maleated castor oil and epoxy resins - Altuncu, Merve Seçkin. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
In this study, castor oil is reacted with maleic anhydride to give maleated castor oil (COMA) which can be used as a biobased epoxy curing agent to enhance the problems of brittle structure of epoxy resins and can undergo free radical polymerization with reactive diluents to give interpenetrating networks which increase mechanical properties. The maleation of castor oil is carried out using the known method developed earlier by our research group with small modifications to increase maleation ratio and shorten the reaction time. Then, COMA is reacted with commercial epoxy resins Bisphenol A diglycidal ether (DGEBPA), Novolac epoxy resin, Heloxy 505 epoxy resin- through its carboxylic acid ends to give thermoset polymers. As a third step, the intact double bonds in polymer structure are polymerized free radically with styrene in the presence of an initiator, azobisisobutyronitrile (AIBN) to give a second interpenetrating network. Characterization of the products is done by IR spectroscopy only due to their crosslinked structure. IR spectra of the polymers are also used to decide the optimum ratio of stoichiometry of COMA/epoxy resin. Thermal stabilities of the samples are analyzed with TGA (Thermogravimetric Analysis). Mechanical properties are determined by surface hardness test by Shore A durameter and three point bending test using the home made instrument produced by our lab.
Keywords: Epoxy resins.; Castor oil -- Therapeutic use.